2007
DOI: 10.1037/0097-7403.33.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Numerical reproduction in pigeons.

Abstract: Pigeons were trained to match the number of responses made during a production phase to the number of keylight flashes (2, 4, or 6) in a previous sample phase. In Experiment 1, there were 2 conditions in which the flashes were programmed to occur at a constant rate or within a constant overall duration. For both conditions, although accuracy was relatively low, responding increased linearly with flash number and coefficients of variation decreased. Positive transfer to novel numbers was obtained only when test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…Yet relatively few studies have directly compared human and nonhuman performance, and those have been limited mostly to nonhuman primates and relative numerosity discriminations (Beran, Johnson-Pynn, & Ready, 2008;Jordan & Brannon, 2006a, b). The aim of the present experiment was to investigate further the processes underlying the nonverbal discrimination of number; it replicates and extends previous research with pigeons by Tan, Grace, Holland, and McLean (2007) and Tan and Grace (2010) with human participants in both relative and absolute numerical tasks.…”
supporting
confidence: 49%
See 3 more Smart Citations
“…Yet relatively few studies have directly compared human and nonhuman performance, and those have been limited mostly to nonhuman primates and relative numerosity discriminations (Beran, Johnson-Pynn, & Ready, 2008;Jordan & Brannon, 2006a, b). The aim of the present experiment was to investigate further the processes underlying the nonverbal discrimination of number; it replicates and extends previous research with pigeons by Tan, Grace, Holland, and McLean (2007) and Tan and Grace (2010) with human participants in both relative and absolute numerical tasks.…”
supporting
confidence: 49%
“…Randomizing the interflash intervals and the total duration of the sample phase controlled the influence of temporal cues. Tan et al (2007) found that response number increased linearly with flash number and showed positive transfer to novel numbers from 1 to 7. Of particular interest, response variability was nonscalar and resembled binomial variability, where relative response variability decreased, instead of remaining constant, as number increased.…”
Section: Present Experimentsmentioning
confidence: 97%
See 2 more Smart Citations
“…The procedure was based on the numerical reproduction task developed by Tan, Grace, Holland, and McLean (2007), modified to investigate relative rather than absolute numerosity discrimination. Pigeons were presented with a sequence of response-dependent keylight flashes, after which they were required to make one of two responses.…”
Section: University Of Canterbury Christchurch New Zealandmentioning
confidence: 99%